2014
DOI: 10.3109/02770903.2014.959129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Th17-related cytokines and IFNγproduction from blood mononuclear cells of moderate and severe asthmatic children reveals methylprednisolone does not decrease IL-22 levels

Abstract: Methylprednisolone downregulated IL-6, IL17A, and IFNγ, but not IL-22, in stimulated PBMCs from asthmatic children indicating that methylprednisolone has no effect on IL-22 production by PBMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The source of the glucocorticoid‐sensitive IL‐17A in those patients was not identified. Glucocorticoid inhibition of IL‐6 could underlie glucocorticoid inhibition of IL‐17A in some asthma patients as methylprednisolone downregulates IL‐6, IL‐17A, and IFN‐γ in stimulated PBMCs from asthmatic children . A recent trial using brodalumab (anti‐IL‐17RA) suggests possible benefits in a select group of patients with highly reversible asthma .…”
Section: Wide‐ranging Glucocorticoid Sensitivity Of Diseases and Th17mentioning
confidence: 99%
“…The source of the glucocorticoid‐sensitive IL‐17A in those patients was not identified. Glucocorticoid inhibition of IL‐6 could underlie glucocorticoid inhibition of IL‐17A in some asthma patients as methylprednisolone downregulates IL‐6, IL‐17A, and IFN‐γ in stimulated PBMCs from asthmatic children . A recent trial using brodalumab (anti‐IL‐17RA) suggests possible benefits in a select group of patients with highly reversible asthma .…”
Section: Wide‐ranging Glucocorticoid Sensitivity Of Diseases and Th17mentioning
confidence: 99%
“…A previous study had found that oral GCs could decrease airway IL-17 in moderate-to-severe asthmatics (17). In vitro research showed that methylprednisolone could downregulate IL-17A levels in the supernatants of PBMCs from children with moderate and severe asthma (18). Fatemeh F et al found that ICS treatment could decrease the number of IL-17 + cells in bronchial submucosa from both atopic and nonatopic asthmatic patients (19).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study had found that oral GCs could decrease airway IL-17 in moderate-to-severe asthmatics ( 17 ). In vitro research showed that methylprednisolone could downregulate IL-17A levels in the supernatants of PBMCs from children with moderate and severe asthma ( 18 ). Fatemeh F et al.…”
Section: Discussionmentioning
confidence: 99%